2006
DOI: 10.1080/00016340600593521
|View full text |Cite
|
Sign up to set email alerts
|

A narrow pelvic outlet increases the risk for emergency cesarean section

Abstract: A narrow pelvic outlet is associated with an increased risk of emergency CS because of protracted labor. A postpartum pelvimetry is recommended and should be used when to decide on route of delivery in forthcoming pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 25 publications
0
23
0
9
Order By: Relevance
“…This does not occur in males. It has been reported that the sacral inclination has an important effect on lower pelvic capacity during childbirth (44,45) and that women who required an emergency Cesarean section had a more narrow pelvic outlet (i.e., an inward-projecting sacrum) than a control group (47).…”
Section: Fig 2 Sexual Dimorphism In the Human Pelvis (A)mentioning
confidence: 99%
“…This does not occur in males. It has been reported that the sacral inclination has an important effect on lower pelvic capacity during childbirth (44,45) and that women who required an emergency Cesarean section had a more narrow pelvic outlet (i.e., an inward-projecting sacrum) than a control group (47).…”
Section: Fig 2 Sexual Dimorphism In the Human Pelvis (A)mentioning
confidence: 99%
“…According to Yong and Ince [19], these proportions of the inlet are similar to the pelvic inlet in males. Parameters of this cluster are similar to the pelvic diameters of the females who had the emergency cesarean section due to dystocia [12,10]. Therefore, this cluster is potentially problematic from an obstetrical perspective.…”
Section: Discussionmentioning
confidence: 66%
“…Stalberg at al. [12] demonstrated that a narrow pelvic midplane is an important reason for the emergency cesarean section. In addition, an inadequate proportion of the pelvic inlet also causes cesarean section [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the conflicting demands of each have created an obstetric dilemma whereby childbirth is rendered difficult as women's hips are only just wide enough to allow an infant to be born (Rosenberg, 1992;Rosenberg & Trevathan, 2002;Wittman & Wall, 2007). Further complications are caused by neonate size remaining relatively constant regardless of variations in maternal size (Butte & King, 2005;Mohanty et al, 2006), which places those with narrow pelvic outlets at greatest risk of Cephalopelvic Disproportion (CPD) (Stålberg, Bodestedt, Lyrenäs, & Axelsson, 2006;Thurnau, Hales, & Morgan, 1992).…”
Section: Introductionmentioning
confidence: 99%